2016
DOI: 10.1590/s0102-865020160050000003
|View full text |Cite
|
Sign up to set email alerts
|

Medication-related osteonecrosis of the jaw. Introduction of a new modified experimental model

Abstract: PURPOSE:To evaluate a modified experimental model for medication-related osteonecrosis of the jaw (MRONJ) through the upper right central incisor extraction followed by intravenous bisphosphonate administration. METHODS:Forty five rats underwent the upper right central incisor tooth extraction were divided in 2 groups: Group I -experimental group, 30 rats received an intravenous administration protocol of zoledronic acid 35μg/kg into the tail vein every two weeks, totalizing four administrations, during eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
3
12
0
2
Order By: Relevance
“…4 and 5). These compare with other findings in mice [23,39], rats [60,61,63] and humans [12,13], including intense leukocyte infiltration, areas of non-vital bone and discrete bone sequestrum.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…4 and 5). These compare with other findings in mice [23,39], rats [60,61,63] and humans [12,13], including intense leukocyte infiltration, areas of non-vital bone and discrete bone sequestrum.…”
Section: Discussionsupporting
confidence: 86%
“…Damage from extensive manipulation of bone, especially in advanced age conditions, does not reflect clinical conditions and could be a confounding factor for the healing process. In comparison with the present study, similar methodology was used in previous studies in rats (upper incisor extraction), in young (3 months old) [63] and senescent animals (20 months old) [61], where animals not necessarily developed clinical findings of MRONJ lesions, but all of them revealed histological features of this pathological conditions [63]. Despite of the differences in animal clinical findings with other studies [61,63], 100% of our ZA samples presented delayed mineralized and organic bone matrix deposition, and also decreased level of collagen maturation along 7 and 21 days ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Given the limitations of a clinical study, the experimental model applied in this investigation was found to be adequate for the proposed analysis. As in previous studies, 11,30 the model of osteonecrosis induced by zoledronic acid was shown to be effective, considering that all the samples presented significant bone changes under computed microtomography. In this context, we retrieved only one experimental study on animals, which conducted microscopic evaluation of the effects of PRP in the treatment of BRONJ, wherein rats subjected to this therapy with zoledronic acid and received PRP presented better bone repair compared to the rats in the treatment group that did not receive PRP.…”
Section: Discussionsupporting
confidence: 66%
“…Thirty (30) Albinus Wistar male rats, with a mean weight of 180 g, underwent surgical procedures for the extraction of upper right incisors following administration of zoledronic acid (Novartis Pharma Stein AG, Stein, Switzerland). The animals were divided into two groups according to the treatment type.…”
Section: Methodsmentioning
confidence: 99%
“… 26 , 48 , 50 53 Twenty-two studies used an intraperitoneal route of application, 15 used subcutaneous, 10 used intravenous, 1 used intramuscular, and 1 used topical. 54 63 The absolute number of studies does not equal 46 because some tested more than one BP or tried different application routes. Table 1 summarizes all conducted studies using rats as test animals.…”
Section: Resultsmentioning
confidence: 99%